Software architecture in action : designing and executing architectural models with SysADL grounded on the OMG SysML standard /: designing and executing architectural models with SysADL grounded on the OMG SysML standard. (2016) - Oquendo, Flavio, 1958-; Leite, Jair; Batista, Thais
No abstract available